2018
DOI: 10.1111/apm.12805
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular proteases of Staphylococcus epidermidis: roles as virulence factors and their participation in biofilm

Abstract: Staphylococci produce a large number of extracellular proteases, some of which are considered as potential virulence factors. Staphylococcus epidermidis is a causative agent of nosocomial infections in medical devices by the formation of biofilms. It has been proposed that proteases contribute to the different stages of biofilm formation. S. epidermidis secretes a small number of extracellular proteases, such as serine protease Esp, cysteine protease EcpA, and metalloprotease SepA that have a relatively low su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 42 publications
(79 reference statements)
0
25
0
1
Order By: Relevance
“…In vitro experiments revealed a very broad activity of both enzymes on the destruction of connective tissue, the evasion of host immunity and the modulation of biofilm integrity [51–57]. A staphopain A-like protease with similar functions, called EcpA, is also expressed by S. epidermidis and other coagulase-negative staphylococci [42, 58, 59]. In contrast, orthologues of the ssp ABC operon have only been identified in S. warneri [60, 61].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments revealed a very broad activity of both enzymes on the destruction of connective tissue, the evasion of host immunity and the modulation of biofilm integrity [51–57]. A staphopain A-like protease with similar functions, called EcpA, is also expressed by S. epidermidis and other coagulase-negative staphylococci [42, 58, 59]. In contrast, orthologues of the ssp ABC operon have only been identified in S. warneri [60, 61].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies have observed the role of these bacterially secreted proteases in influencing polymicrobial dynamics. Previous investigations have shown that in competition for nasal mucosa between Staphylococcus aureus and Staphylococcus epidermidis, S. epidermidis strains that produce the serine protease Esp are able to outcompete and eradicate nasal colonization of S. aureus (32,33).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the proteases of the species Stenotrophomonas maltophilia, Pseudomonas putida, Klebsiella oxytoca, and Pantoea dispersa, identified in this work as proteases producers (Table 1), have already been characterized (Tondo et al, 2004;Nicodème et al, 2005;Gohel et al, 2007;Ribitsch et al, 2012). With respect to the genera Burkholderia, Staphylococcus, and Ochrobactrum, the proteases of the species Burkholderia pseudomallei, Staphylococcus aureus, Staphylococcus epidermidis, and Ochrobactrum anthropi were also characterized (Bompard-Gilles et al, 2000;Shaw et al, 2004;Chin et al, 2007;Martínez-García et al, 2018). Despite the production of proteases by the genera Isoptericola, Massilia, and Sphingomonas being also described in the literature (Lindquist et al, 2003;Willsey & Wargo, 2015, Bibi et al, 2017, none has been studied so far, and this is the first report about the species Staphylococcus hominis and Massilia timonae as protease producers (Table 1).…”
Section: Discussionmentioning
confidence: 70%